3D elastoplastic damage model for concrete based on novel decomposition of stress. (September 2016) - Zhang, Ji; Li, Jie; Ju, J. Woody
Abstract: This study aims to develop a versatile constitutive framework for concrete that can be used in various stress states and under reversed cyclic loading. A multi-axial compression stress state is decomposed into a hydrostatic confining part and a biaxial net part to distinguish concrete behavior in triaxial and biaxial compression while preserving their similarity. This novel decomposition is combined with the positive–negative decomposition of stress, and on its basis is developed a 3D elastoplastic damage model. The suppression on damage of the net part of stress from the presence of the confining part is introduced through an increase in microscopic fracture strains, and confining effects in ductility and lateral deformation are introduced, respectively, by hardening slowdown and dilation reduction. In the meantime, independent damage/plasticity evolution in tension and compression is incorporated in the proposed 3D model with two damage variables and two hardening variables. An elastic–plastic–damage operator split integration algorithm with the backward Euler return mapping is derived, and a series of numerical simulations are carried out in comparison with tests under uniaxial, biaxial, pseudo-triaxial, and true triaxial loading with satisfactory agreement.